TINJAUAN HUKUM TERHADAP IZIN PENEBANGAN POHON PADA DINAS PERTAMANAN KOTA SAMARINDA BERDASARKAN PERATURAN DAERAH NOMOR 19 TAHUN 2013 TENTANG PENGHIJAUAN - Dian Utari (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
Abstract    The existence of natural resources, water, land and other resources that determine the daily human activities. Man can not live without air and water. Conversely there is also a very human activity affecting the availability of resources and the surrounding environment.Article 1 paragraph 2 of Regulation of the Minister of the Interior No. 1 Year 2007 on Spatial Planning Green Open Urban Area reads "Green Open Space Urban Area hereinafter abbreviated RTHKP is part of the open space an urban area populated by plants and crops to support the benefits of social, cultural , economy and aesthetics ".       Criminal sanctions against the misuse of the felling of trees can be run in accordance with the Regional Regulation No. 13 In 2013 for every offense committed may be subject to criminal sanctions.